STRATEGI PENCEGAHAN BAHAYA KONTEN RADIKAL DAN PORNOGRAFI DI INTERNET - Nurdin Nurdin; Mohammad Nur Ahsan (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2016)
Internet does not only provide positive information but also depict negative information and images such as radical and pornography. Previous studies found that most of young citizens have accessed online radical and pornography contents. This caused massive impacts on their behaviour and society life. Instead the negative impacts have been addressed in previous studies, little is known how those impacts should be eliminated. Through an intensive literature review approach, this study, therefore, is intended to provide insight on how the impacts of online radicalism and pornography should be prevented or eliminated. The author usd secondary data from various online data sources such as journals, mass media sites, and other relevant sites. The results show that online radical contents can trigger society to be radical and lack tolerant toward social life. Meanwhile, online pornography contents cause young generation to lack sensitive toward their marriage life and cause them to practice abnormal sexual life. This study also found that the impacts can be prevented and eliminated through increasing Muslim leaders and da’i roles in spreading intensive Islamic values into society, increasing government actor roles to monitor and block such contents, and providing training for society to block negative sites on their own. In conclusion, online radical and pornography contents can impact society life regarding increasing violent and intolerant behavior, while online pornography contents can cause lack sexual sensitivity and increase violent toward women. However, such impacts can be prevented and eliminated through increasing da’i roles, increasing government actor roles in monitoring the sites, and improving citizen skills to block the sites.